Adoption of Dryland Farming Practices by the Farmers of Bijapur District - V. G. Bavalatti; B. Sundaraswamy (Indian Journal of Extension Education, 1990)
In the present study an attempt is made to examine where do we stand in relation to the adoption of dryland farming practices and to identify relationship between the adoption and personal characteristics of the farmers.